Ancaman Keamanan pada Transport Layer Security - Muhamad Fadhli; Fityan Ali Munshi; Taufik Adi Wicaksono (Ultima Computing : Jurnal Sistem Komputer, 2015)
Secure Socket Layer (SSL) also known as Transfer Layer Security (TLS) is de facto standard for web security. It provides confidentiality and integrity of information in transit across the public networks using their powerful cipher suites but it still contains some loopholes or flaws in its foundation. In this paper we discuss TLS standard along with various attacks found in recent years, such as BEAST, CRIME, BREACH, Lucky 13, and their proposed mitigation. Index Terms— Attack, Compression, Mitigation, Security, TLS.